Eryptosis - the Neglected Cause of Anemia in End Stage Renal Disease - Florian Lang; Rosi Bissinger; Majed Abed; Ferruh Artunc (Karger Publishers, 2017)
End stage renal disease (ESRD) invariably leads to anemia which has been mainly attributed to compromised release of erythropoietin from the defective kidneys with subsequent impairment of erythropoiesis. However, erythropoietin replacement only partially reverses anemia pointing to the involvement of additional mechanisms. As shown more recently, anemia of ESRD is indeed in large part a result of accelerated erythrocyte loss due to suicidal erythrocyte death or eryptosis, characterized by cell shrinkage and cell membrane scrambling with phosphatidylserine translocation to the cell surface. Phosphatidylserine exposing erythrocytes are bound to and engulfed by macrophages and are thus rapidly cleared from circulating blood. If the loss of erythrocytes cannot be fully compensated by enhanced erythropoiesis, stimulation of eryptosis leads to anemia. Eryptotic erythrocytes may further adhere to the vascular wall and thus impair microcirculation. Stimulators of eryptosis include complement, hyperosmotic shock, energy depletion, oxidative stress, and a wide variety of xenobiotics. Signaling involved in the stimulation of eryptosis includes increase of cytosolic Ca2+ activity, ceramide, caspases, calpain, p38 kinase, protein kinase C, Janus-activated kinase 3, casein kinase 1α, and cyclin-dependent kinase 4. Eryptosis is inhibited by AMP-activated kinase, p21-activated kinase 2, cGMP-dependent protein kinase, mitogen- and stress-activated kinase MSK1/2, and some illdefined tyrosine kinases. In ESRD eryptosis is stimulated at least in part by a plasma component, as it is triggered by exposure of erythrocytes from healthy individuals to plasma from ESRD patients. Several eryptosis-stimulating uremic toxins have been identified, such as vanadate, acrolein, methylglyoxal, indoxyl sulfate, indole-3-acetic acid and phosphate. Attempts to fully reverse anemia in ESRD with excessive stimulation of erythropoiesis enhances the number of circulating suicidal erythrocytes and bears the risk of interference with micocirculation, At least in theory, anemia in ESRD could preferably be treated with replacement of erythropoietin and additional inhibition of eryptosis thus avoiding eryptosis-induced impairment of microcirculation. A variety of eryptosis inhibitors have been identified, their efficacy in ESRD remains, however, to be shown.